Construction Industry Human Capital Investment In Industrial Revolution 4.0 - Jagenmohan Rao, Venkatasverarav (2020)
The role of human capital in Malaysian construction industry is very often underestimated. The construction industry considers human capital as executory force of projects instead of force that builds competitiveness of business. Human capital is highlighted playing a major role in creating market advantage. However, there are many attributes of human capital that need to be paid attention to create the aforesaid market advantage. The emergence of Industrial Revolution 4.0, many services in the industry are automated or digitalised. Therefore, it is limiting the human involvement significantly. In this research five (5) element of human capitals are identified which required for an organisation survive along the IR 4.0. The five elements of human capitals are skill, knowledge, experience, ethics and emotional qualities. The research is aimed to provided the most and least required human capital. The theoretical framework was established through the literature reviews. The questionnaires were setup based on the theoretical framework to collect the data from industry participants. In return ninety-two (92) respondents has responded to the questionnaires. Based on the final outcome of this study, skill, knowledge, and ethics are received welcoming response from the participants. The human capital elements such as experience and emotional qualities receives less supportive responses. The research is benefitted to the construction industry such a way that, it identifies the human capital that required to be focused more. In society it set a guidance to community to make substantial investment to the skills of an individual. The research limitation is, the responses are majorly from the executive level. The responses from the C-level executives and responses from government link companies and public listed companies are not that much as it seems only few are available in market. At the end, the research recommends to synthesise the study of each human capital into more specific with larger sample size.